The library at Hellebore - Khaw, Cassandra (Nightfire, Tor Publishing Group, 2025)
The Hellebore Technical Institute for the Gifted is the premier academy for the dangerously powerful: the Anti-Christs and Ragnaroks, the world-eaters and apocalypse-makers. Hellebore promises redemption, acceptance, and a normal life after graduation. At least, that's what Alessa Li is told when she's kidnapped and forcibly enrolled. But there's more to Hellebore than meets the eye. On graduation day, the faculty go on a ravenous rampage, feasting on Alessa's class. Only Alessa and a group of her classmates escape the carnage. Trapped in the school's library, they must offer a human sacrifice every night, or else the faculty will break down the door and kill everyone. Can they band together and survive, or will the faculty eat its fill?